The Green Revolution in India, 1967-1970 Search from Setup - جمعة وجر كفاح; عبد الجبار عبود مثنى (Al-Adab Journal, 2018)
The Research Explores the Green Revolution Witnessed by India Between 1967 and 1970, which has become a Watershed in India’s Economic History due to the Important Results achieved by that Revolution. The Department of Research on three topics Dealt with the Reasons that Called for the adoption of the Green Revolution, while the Second topic Focused on the Revolution and the Most Important Developments, the Third Section Specializes in Evaluating the Revolution in Terms of Pros and Cons.